Suitable raotstocks for pear troes. I. Quince tree cv. Japão as a potential material for pear troe grown ar the highiands of south regian of Minas Gerais state, Brazil. - Ramos, José Darlan; Souza, Maurício de; Pasqual, Moacir (Pesquisa Agropecuaria Brasileira, 2014)
The use of grafted pear seedlings by growers at south region of Minas Gerais state is not a common cultural practice. This is due to both low survival efficiency of the rootstocks and lack of suitable rootstocks genotypes which would yield large amount of highly viable seeds to fulfill the needs of a program aimed at the production of vigorous pear seedlings. The "Japão" quince tree in addition to yield numerous seeds per fruit, bears some favorable charaeteristics such as a remarkable axial root system (different from that of pear cultivars propagated by rooting cuttings), trait, and most important of ali, the ability to grow vigorously as seedlings. This, quince tree can be a solution to the rootstocks shortage concerning pear tree orchard formation at the region on focus. The present work was to show the development of quince tree rootstocks for pears ia the south region of Minas Gerais, Brazil